The Domination of Political Power over Legal Politics in the Deliberation of the Asset Forfeiture Bill - KMS Herman; Pribowo, Johan Budi Sapto; Rumondor, Nova Ernny; Zamri, Hasby Muhammad; Budiawan, Taufik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Asset Forfeiture Bill (RUU Perampasan Aset) is an important instrument in strengthening the eradication of corruption crimes, as it provides a legal basis for the state to seize assets resulting from corruption without having to wait for a legally binding criminal verdict. Although it was proposed as early as 2010 and included in the National Legislation Program (Prolegnas) 2015–2019, the discussion of the bill has often been delayed. In 2023, the government and the House of Representatives (DPR) included the Asset Forfeiture Bill in the 2023 Prolegnas. However, until the end of the DPR RI’s and the government’s 2019–2024 term, the bill had yet to be passed. This research aims to analyze the domination of political power in the lawmaking process concerning the Asset Forfeiture Bill. The study uses a normative juridical method with a literature study approach. The issues examined include: (1) the legal condition of asset forfeiture in Indonesia; (2) the dynamics of the debate that have caused delays in the passage of the Asset Forfeiture Bill; and (3) the political factors that influence the stagnation of the bill's ratification amid strong public pressure.The results of the study show: first, that the legal regulation of asset forfeiture in Indonesia still experiences a significant normative void. Although regulations related to the forfeiture of assets resulting from corruption are stipulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, there is no comprehensive provision regarding asset forfeiture from perpetrators who have fled, cannot be found, or have died without heirs. Therefore, special regulations on asset forfeiture are needed, including the management of ownerless assets as state assets. Second, the delay in the discussion of the Asset Forfeiture Bill is influenced by the inconsistency of legislative priorities in the DPR, concerns about potential human rights violations, and the intervention of political and economic interests involving various parties. Third, although there is strong public pressure, internal political dynamics within the DPR remain the main obstacle. Disagreements between factions, concerns over the political implications of regulatory implementation, and the absence of consensus on a legal model that aligns with human rights principles are dominant factors slowing the legislative process